Synthesis, photophysical and photochemical properties of novel tetra substituted metal free and metallophthalocyanines bearing triazine units - (:unkn) unknown (ELSEVIER SCIENCE SA, 2013)
The synthesis and characterization of peripherally tetra 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(hexyloxy) phenoxy substituted metal-free (4), zinc(II) (5), oxotitanium(IV) (6), lead(II) (7), nickel(II) (8), copper(II) (9) and cobalt(II) (10) were described for the first time in this study. The photophysical and photochemical properties of metal-free (4), zinc(II) (5), oxotitanium(IV) (6) and lead(II) (7) phthalocyanines were investigated in toluene. The synthesized nickel(II) (8), copper(II) (9) and cobalt(II) (10) phthalocyanines were not evaluated for this purpose because of paramagnetic behavior of the central transition metals in the cavity for these complexes. General trends were described for photodegradation, singlet oxygen and fluorescence quantum yields, and fluorescence lifetimes of these compounds in toluene. The influence of the variety of central metal ions in phthalocyanine cavity on the spectroscopic, photophysical and photochemical properties were also determined. The fluorescence quenching behavior of the studied peripherally tetra 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(hexyloxy) phenoxy substituted metal-free (4), zinc(II) (5), oxotitanium(IV) (6) and lead(II) (7) by the addition of 1,4-benzoquinone were also studied. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Triazine; Photophysical; Photochemical; Singlet oxygen; PHTHALOCYANINES; SOLVENT